2010
DOI: 10.1161/circresaha.109.201103
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ROCK1 Branch of the Transforming Growth Factor-β Pathway Contributes to RAGE-Dependent Acceleration of Atherosclerosis in Diabetic ApoE-Null Mice

Abstract: Rationale: The multiligand RAGE (receptor for advanced glycation end products) contributes to atherosclerosis in apolipoprotein (Apo)E-null mice. Objective: To delineate the specific mechanisms by which RAGE accelerated atherosclerosis, we performed Affymetrix gene expression arrays on aortas of nondiabetic and diabetic ApoE-null mice expressing RAGE or devoid of RAGE at nine weeks of age, as this reflected a time point at which frank atherosclerotic lesions were not yet present, but that we would be able to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 38 publications
1
67
1
Order By: Relevance
“…In these mice, RAGE protein and mRNA expression is increased in the vascular endothelium [64,99]. We [64] and others [66,100] have recently shown that in diabetic RAGE − / − /apoE − / − double KO (knockout) mice, the absence of RAGE was associated with a significant attenuation of atherosclerotic plaque accumulation. The reduction in atherogenesis is associated with decreased accumulation of macrophages and T-lymphocytes, reduced aortic expression of the NFkB subunit p65 and decreased expression of inflammatory cytokines and adhesion molecules, including VCAM-1, MCP-1 and certain NADPH oxidase subunits such as gp91 phox , p47 phox and rac-1.…”
Section: Age/rage In In Vivo Modelsmentioning
confidence: 85%
See 1 more Smart Citation
“…In these mice, RAGE protein and mRNA expression is increased in the vascular endothelium [64,99]. We [64] and others [66,100] have recently shown that in diabetic RAGE − / − /apoE − / − double KO (knockout) mice, the absence of RAGE was associated with a significant attenuation of atherosclerotic plaque accumulation. The reduction in atherogenesis is associated with decreased accumulation of macrophages and T-lymphocytes, reduced aortic expression of the NFkB subunit p65 and decreased expression of inflammatory cytokines and adhesion molecules, including VCAM-1, MCP-1 and certain NADPH oxidase subunits such as gp91 phox , p47 phox and rac-1.…”
Section: Age/rage In In Vivo Modelsmentioning
confidence: 85%
“…NF-κB up-regulates multiple cellular signalling cascades, such as NADPH oxidase, CDC42, RAC-1, the MAPKs, p21 ras , ERKs p38 MAPK and PKC [56,57,59,60]. This causes increased production of numerous growth factors and cytokines including VCAM-1, ICAM-1 (intercellular adhesion molecule-1), E-selectin, TGF-β1 (transforming growth factor-β1), CTGF (connective tissue growth factor), PDGF (plateletderived growth factor), TNF-α (tumour necrosis factor-α), IL-1 and IL-6 [61][62][63][64][65][66], all of these molecules having been implicated in the development and progression of a variety of diabetic complications.…”
Section: Rage and Its Ligandsmentioning
confidence: 99%
“…75). In vascular cells, this interaction results in the activation of a number of intracellular pathways, including PKC/Rho (16,17,76). The prototype therapeutic agent aminoguanidine is known to prevent AGE formation by reacting with derivatives of early glycation products, such as 3-deoxyg-lucosone (reviewed in Ref.…”
Section: No Diabetesmentioning
confidence: 99%
“…The underlying mechanism behind this effect is in part due to activation of the PKC/Rho/Rho-kinase pathway by glucose, which results in calcium sensitization by inhibiting myosin light chain phosphatase (12)(13)(14)(15). The activation of PKC and Rho in smooth muscle by hyperglycemia is thought to be dependent on the formation of advanced glycation end products (AGEs) 2 (16,17). In addition to calcium sensitization, activation of the Rho/ Rho-kinase pathway in vascular smooth muscle cells promotes actin polymerization, an effect that plays a major role in the regulation of smooth muscle gene expression and activates myocardin-related transcription factors (MRTFs, also known as MKL1/2), co-factors to serum response factor (SRF) (18,19).…”
mentioning
confidence: 99%
“…Recently, it has been reported that Src tyrosine kinase activated by RAGE is involved in a series of cellular responses in porcine aortic VSMC, including activation of MAP kinases and STAT3 as well as NF-B-dependent proinflammatory gene expression 21) . Very recently, it has been shown that RAGE activation is involved in the activation of the TGF--ROCK1 pathway in mouse aortic VSMC 22) . In contrast, several previous studies have shown that cultured VSMC barely expressing RAGE were unable to respond to RAGE ligands 5,23) .…”
Section: Discussionmentioning
confidence: 99%